Culture and Behavior Boost Productivity While Loyalty Lowers It in Indonesia: Budaya dan Perilaku Meningkatkan Produktivitas, Sementara Loyalitas Menurunkannya di Indonesia - Yelin Febira Nandalia; Vera Firdaus (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the relationships between organizational culture, job loyalty, work behavior, and employee productivity at the SAMSAT Sidoarjo Office, with job satisfaction as a mediating factor. Using a quantitative approach and total sampling, data were collected from 130 employees via questionnaires and analyzed using Smart Partial Least Square (SmartPLS). The results reveal that organizational culture and work behavior positively impact productivity, while job loyalty has a negative effect. All three variables positively influence job satisfaction, which in turn enhances productivity. The findings underscore the importance of fostering a supportive organizational culture and positive work behaviors to boost employee satisfaction and productivity. Highlights: 1. Positive Influence: Culture and behavior boost productivity and satisfaction. 2. Negative Impact: Job loyalty decreases productivity. 3. Mediating Role: Job satisfaction mediates culture, loyalty, behavior impacts on productivity. Keywords: Organizational culture, job loyalty, work behavior, employee productivity, job satisfaction